Nonnus of Panopolis in Context II: Poetry, Religion, and Society: Proceedings of the International Conferenceon Nonnus of Panopolis, 26th–29th September 2013, University of Vienna,Austria - Bannert, Herbert; Kröll, Nicole (Mnemosyne, 2018)
Front Matter -- Nonnus, from Our Time to His. A Retrospective Glance at Nonnian Studies (Notably the Dionysiaca) since the 1930s /Pierre Chuvin -- The Cadmus Narrative in Nonnus’ Dionysiaca /Michael Paschalis -- Dionysus, Ampelus, and Mythological Examples in Nonnus’ Dionysiaca /Katerina Carvounis -- Nonnus’ Catalogic Strategies. A Preliminary Approach to the Dionysiaca /Laura Miguélez-Cavero -- Mythographic Lists as Sources of the Dionysiaca of Nonnus /Simon Zuenelli -- Similes and Comparisons in the Dionysiaca: Imitation, Innovation, Erudition /Camille Geisz -- What a Wonder! Looking through the Text-Internal Observer’s Eyes in Nonnus’ Dionysiaca /Berenice Verhelst -- The Tablets of Harmonia and the Role of Poet and Reader in the Dionysiaca /Joshua Fincher -- In the Beginning was the Voice /Jane L. Lightfoot -- Words and Their Meaning. On the Chronology of the Paraphrasis of St John’s Gospel /Fabian Sieber -- Characterization of Persons and Groups of Persons in the Metabole /Maria Ypsilanti and Laura Franco -- The Wise Mysteries of the Sacrificial Hour. Nonnus’ Exegesis of John 4.23 /Filip Doroszewski -- Flumina de ventre eius fluent aquae vivae. Nonnus’ Paraphrase 7.143–148, John 7.37–38, and the Symbolism of Living Water /Roberta Franchi -- The Staphylus Episode. Nonnus and the Secret Gospel of Mark /Konstantinos Spanoudakis -- Nonnus and Pindar /Daria Gigli Piccardi -- Christodorus of Coptus on the Statues in the Baths of Zeuxippus at Constantinople. Text and Context /Mary Whitby -- An Attempt to Remove the Asia-Europe Opposition. Καύκασος in the Dionysiaca of Nonnus of Panopolis /Nestan Egetashvili -- Metrische Beobachtungen zum Hexameter der Disticha des Kyklos /Claudio De Stefani -- Die Versuchung des Nonnos. Der Mythos als Brücke zwischen Heiden- und Christentum /Domenico Accorinti -- The Quest for Nonnus’ Life. From Scholarship to Fiction /David Hernández de la Fuente -- Ut poesis pictura. Nonnus’ Europa Episode as Poetry and Painting /Robert Shorrock -- Note on Panopolis in Upper Egypt (Now Akhmim, Governorate Sohag) in Late Antiquity and After /Michael Zach -- Bibliography -- Indexes.